Endocytosis and Endosomal Trafficking of DNA After Gene Electrotransfer In Vitro - Christelle Rosazza; Hendrik Deschout; Annette Buntz; Kevin Braeckmans; Marie-Pierre Rols; Andreas Zumbusch (Elsevier, 2016)
DNA electrotransfer is a successful technique for gene delivery into cells and represents an attractive alternative to virus-based methods for clinical applications including gene therapy and DNA vaccination. However, little is currently known about the mechanisms governing DNA internalization and its fate inside cells. The objectives of this work were to investigate the role of endocytosis and to quantify the contribution of different routes of cellular trafficking during DNA electrotransfer. To pursue these objectives, we performed flow cytometry and single-particle fluorescence microscopy experiments using inhibitors of endocytosis and endosomal markers. Our results show that ≃50% of DNA is internalized by caveolin/raft-mediated endocytosis, 25% by clathrin-mediated endocytosis, and 25% by macropinocytosis. During active transport, DNA is routed through multiple endosomal compartments with, in the hour following electrotransfer, 70% found in Rab5 structures, 50% in Rab11-containing organelles and 30% in Rab9 compartments. Later, 60% of DNA colocalizes with Lamp1 vesicles. Because these molecular markers can overlap while following organelles through several steps of trafficking, the percentages do not sum up to 100%. We conclude that electrotransferred DNA uses the classical endosomal trafficking pathways. Our results are important for a generalized understanding of gene electrotransfer, which is crucial for its safe use in clinics.